Charles Darwin’s “Scientific Wit”: Incongruity, Species Fixity & The Nonsense of Looking - Lee, Louise (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2016)
Critics have often noted Darwin’s enthusiastic curiosity (Beer, Levine, Amigoni, Schmitt, Browne) in the Journal of Researches (1839)—particularly its “intensely libidinous” nature (Beer)—but his “strange antics” and numerous instances of “amusement” have been treated as little more than biographical gloss, or charming digressions on the way to a much larger story. But re-reading these understatedly comic episodes through the interpretive prism of incongruity produces a new set of emphases, and intellectual and affective affinities. For, like Michel Foucault’s laughter at the beginning of The Order of Things (1966), Darwin’s “scientific wit” has distinctly taxonomic implications. Incongruity figures the splicing of two previously un-apprehended interpretive frames, a kink in the logic of expectation. While Darwin later naturalizes (rather than spectacularizes) incongruity into his scientific method, in its first iteration in the Journal, it performs vital cultural and aesthetic work: upturning sublimity and delivering detail and present-ness rather than vastness and transcendental awe. Building on Arthur Koestler’s theory of “bisociation”, I argue that incongruity—a gentlemanly and Enlightenment theory of comedy that is fundamentally horizontal rather than vertical in its purview—operates by making Darwin’s own previous expectations, rather than any object, animal or person, the butt of the joke. The “clash” of comic frames at the point of observation limns incongruity’s usefulness as a form of visually self-stimulating agon. These “shifts of attention” (Koestler), I propose, have significant implications in his early evolutionary theorizing: gesturing towards Darwin’s own “nonsense” aesthetic: one that is highly suggestive of non-essentialist approaches to species thinking.